(Dimethylamino)borylene and Related Complexes of Electron-Rich Metal Fragments: Generation of Nucleophile-Resistant Cations by Spontaneous Halide Ejection - Addy, D; Phillips, N; Pierce, G; Vidovic, D; Kraemer, T; Mallick, D; Jemmis, E; Reid, G; Aldridge, S (2012)
Spontaneous halide ejection from a three-coordinate Lewis acid has been shown to offer a remarkable new route to cationic metal complexes featuring a linear, multiply bonded boron-donor ligand. The exploitation of electron-rich [CpM(PR 3) 2] fragments within boryl systems of the type L nMB(hal)NR 2 leads to the spontaneous formation in polar solvents of chemically robust borylene complexes, [L nM(BNR 2)] +, with exceptionally low electrophilicity and short M-B bonds. This is reflected by M-B distances (ca. 1.80 Å for FeB systems) which are more akin to alkyl-/aryl-substituted borylene complexes and, perhaps most strikingly, by the very low exothermicity associated with the binding of pyridine to the two-coordinate boron center (ΔH = -7.4 kcal mol -1, cf. -40.7 kcal mol -1 for BCl 3). Despite the strong π electron release from the metal fragment implied by this suppressed reactivity and by such short M-B bonds, the barrier to rotation about the Fe=B bond in the unsymmetrical variant [CpFe(dmpe)(BNC 6H 4OMe-4Me)] + is found to be very small (ca. 2.9 kcal mol -1). This apparent contradiction is rationalized by the orthogonal orientations of the HOMO and HOMO-2 orbitals of the [CpML 2] + fragment, which mean that the M-B π interaction does not fall to zero even in the highest energy conformation. © 2012 American Chemical Society.